Associations between endogenous sex hormone levels and adipokine levels in the Multi-Ethnic Study of Atherosclerosis - Varma, Bhavya; Ogunmoroti, Oluseye; Ndumele, Chiadi E.; Kazzi, Brigitte; Rodriquez, Carla P.; Osibogun, Olatokunbo; Allison, Matthew A.; Bertoni, Alain G.; Michos, Erin D. (Frontiers in Cardiovascular Medicine, 2023)
Background: Differences in sex hormone levels contribute to differences in cardiovascular disease (CVD) risk. Adipokines play a role in cardiometabolic pathways and have differing associations with CVD. Adipokine levels differ by sex; however, the association between sex hormone profiles and adipokines is not well established. We hypothesized that a more androgenic sex hormone profile would be associated with higher leptin and resistin and lower adiponectin levels among postmenopausal women, with the opposite associations in men. Methods: We performed an analysis of 1,811 adults in the Multi-Ethnic Study of Atherosclerosis who had both sex hormones and adipokines measured an average of 2.6 years apart. Sex hormones [Testosterone (T), estradiol (E2), sex hormone binding globulin (SHBG), and dehydroepiandrosterone (DHEA)] were measured at exam 1; free T was estimated. Serum adipokines [leptin, resistin, adiponectin] were measured at exams 2 or 3. We used multivariable linear regression to examine the cross-sectional associations between sex hormones and adipokines. Results: The mean (SD) age was 63 (10) years, 48% were women; 59% non-White participants. For leptin, after adjusting for demographics only, higher free T and lower SHBG, were associated with higher leptin in women; this association was attenuated after further covariate adjustment. However in men, higher free T and lower SHBG were associated with greater leptin levels in fully-adjusted models. For adiponectin, lower free T and higher SHBG were associated with greater adiponectin in both women and men after adjustment for CVD risk factors. For resistin, no significant association was found women, but an inverse association with total T and bioT was seen in men. Conclusion: Overall, these results further suggest a more androgenic sex profile (higher free T and lower SHBG) is associated with a less favorable adipokine pattern. These findings may provide mechanistic insight into the interplay between sex hormones, adipokines, and CVD risk.